Pengaruh Pemberian Konsentrasi Pupuk Organik Cair Daun Kelor terhadap Pertumbuhan dan Kualitas Hasil Tanaman Kangkung Darat (Ipomoea reptans Poir) - Putri, Iswahyuni Hartanto; Mahendra, Made Sudiana; Mayun, Ida Ayu (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024), 2024)
The Effect of The Concentration of Moringa Leaves Organic Liquid Fertilizer on The Growth and Yield Quality of Land Kale Plants ( Ipomoea reptans Poir ).   The land kale plant is a vegetable plant that has many benefits and is a source of fiber, protein, vitamin A, iron and calcium. This study aims to determine the effect of giving the concentration of moringa leaves organic liquid fertilizer (OLF) on the growth and yield quality of land kale plants .  This study used a completely randomized design (CRD) with 6 treatments and repeated 4 times to obtain 24 experimental units. For the experimental treatment the OLF concentrations of Moringa leaves used were as follows: 0 ml/l water, 50 ml/l water, 100 ml/l water, 150 ml/l water, 200 ml/l water and 250 ml/l water. Parameters observed in this study were leaf chlorophyll content, plant height (7, 14, 21 and 28 dap), number of leaves (7, 14, 21 and 28 dap), leaf area, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight and root shoot ratio. The results of this study indicate that the application of OLF concentrations of moringa leaves to land kale plants had a very significant effect on the parameters of leaf chlorophyll content, plant height 21 and 28 dap, number of leaves 28 dap, leaf area and shoot dry weight and had a significant effect on parameters of shoot fresh weight and root dry weight. Concentration of 250 ml/l is the best concentration of moringa leaves OLF which gives the best growth and yield quality of land kale plants. Leaf chlorophyll content increased 57,1%, plant height at 28 dap 61.63%, number of leaves at 28 days after 66.89%, leaf area 207,78% shoot fresh weight 216.43% compared to control.